The Immunomodulatory Effects of Herbal Supplements in Poultry - Michael, Catherine (Animal Health Journal, 2024)
Purpose: The general purpose of the study was to explore the immunomodulatory effects of herbal supplements in poultry. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to immunomodulatory effects of herbal supplements in poultry. Preliminary empirical review revealed that herbal extracts enhanced immune parameters, such as lymphocyte proliferation and cytokine production, suggesting their potential to improve poultry health and disease resistance. The diverse mechanisms of action of phytochemicals underscored the complexity of herbal supplements' effects on poultry immunity, while considerations such as formulation and environmental factors influenced their efficacy. Overall, while further research is warranted to optimize formulations and deepen our understanding of mechanisms, herbal supplements show considerable promise as alternatives to conventional additives in poultry production, offering holistic and sustainable approaches to enhancing poultry health and welfare. Unique Contribution to Theory, Practice and Policy: The Systems Biology theory, Ecological Systems theory and Ethnopharmacology theory may be used to anchor future studies on immunomodulatory effects of herbal supplements in poultry. The study provided recommendations that contributed to theory, practice, and policy in poultry production and animal health. The findings advanced theoretical knowledge by elucidating the complex interactions between phytochemicals and the avian immune system. In practice, recommendations supported the incorporation of herbal supplements into poultry diets to promote immune health and disease resistance, benefiting poultry producers, veterinarians, and feed manufacturers. Moreover, policy recommendations advocated for regulatory frameworks supporting the use of herbal supplements and education initiatives aimed at enhancing stakeholder awareness and understanding. Collaboration between academia, industry, and government agencies was recommended to further research and innovation, while international cooperation facilitated knowledge exchange and harmonization of standards. Keywords: Immunomodulatory, Herbal Supplements, Poultry, Phytochemicals, Immune Function, Sustainable, Regulation, Collaboration, International Cooperation